2018
DOI: 10.3390/molecules23030511
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Solvents for the Dissolution, Shaping and Derivatization of Cellulose: Quaternary Ammonium Electrolytes and their Solutions in Water and Molecular Solvents

Abstract: There is a sustained interest in developing solvents for physically dissolving cellulose, i.e., without covalent bond formation. The use of ionic liquids, ILs, has generated much interest because of their structural versatility that results in efficiency as cellulose solvents. Despite some limitations, imidazole-based ILs have received most of the scientific community’s attention. The objective of the present review is to show the advantages of using quaternary ammonium electrolytes, QAEs, including salts of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 217 publications
0
48
0
Order By: Relevance
“…Below, we focus our discussion of these issues on ionic liquids (ILs), and two of their sub-classes: quaternary ammonium electrolytes (QAEs), and salts of super-bases. Additional discussion on aspects of dissolution of cellulose and other natural polymers in ILs and applications of the solutions obtained therefrom can be found elsewhere [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Ionic Liquids Quaternary Ammonium Electrolytes and Salts Omentioning
confidence: 99%
“…Below, we focus our discussion of these issues on ionic liquids (ILs), and two of their sub-classes: quaternary ammonium electrolytes (QAEs), and salts of super-bases. Additional discussion on aspects of dissolution of cellulose and other natural polymers in ILs and applications of the solutions obtained therefrom can be found elsewhere [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Ionic Liquids Quaternary Ammonium Electrolytes and Salts Omentioning
confidence: 99%
“…Solubility of cellulose in imidazolium‐based ILs has been covered in review articles and book chapters. [ 7,110,111 ] As discussed above, the choice of cation and anion affects cellulose dissolution and bears on environmental aspects and sustainability of the process. [ 112 ] Common imidazolium‐based ILs, such as BuMeImCl, 1‐ethyl‐3‐methylimidazolium chloride and 1‐ethyl‐3‐methylimidazolium acetate were compared with NMMO as spin dopes for shaping cellulose into fibers.…”
Section: Regeneration Of Cellulose In Different Physical Formsmentioning
confidence: 99%
“…Other ILs, such as QAEs, were recently explored as solvents for regeneration of cellulose into fibers. [ 7 ] For fiber spinning, solvents based on mixtures of tetra( n ‐butyl)ammonium acetate (Bu 4 AOAc) in combination with DMSO have shown some promise. Thus, 5 wt% bamboo pulp dissolved in Bu 4 AOAc/DMSO (1:4 mass ratio) was regenerated as fibers via wet spinning, using ethanol as coagulation medium.…”
Section: Regeneration Of Cellulose In Different Physical Formsmentioning
confidence: 99%
“…[24] Indeed, the high ionic strength of the ILs allows interrupting the inter-and intramolecular hydrogen-bondingbased interactions in cellulose chains. [24][25][26] Some studies with ILs outline that the nature of the anion is responsible for the dissolution of cellulose. However, it was also shown that especially the structure of the cation influences the solvation process, too.…”
Section: Introductionmentioning
confidence: 99%